Fluoxetine increased adult neurogenesis is mediated by 5-HT3 receptor. (31st January 2023) - Olivas-Cano, I.; Rodriguez-Andreu, J.M.; Blasco-Ibañez, J.M.; Crespo, C.; Nácher, J.; Varea, E.
Highlights: The 5-HT3 receptor is expressed in neuronal progenitors in the SGZ. Fluoxetine-induced adult hippocampal neurogenesis is mediated by 5-HT3 receptors. 5-HT3 receptor is responsible for structural plasticity mediated by fluoxetine. Abstract: Adult neurogenesis is an aspect of structural plasticity that remains active during adulthood in some brain regions. One of them is the subgranular zone (SGZ) of the dentate gyrus of the hippocampus. Adult neurogenesis is reduced by different factors and in disorders of the CNS, including major depression. Antidepressant treatments, such as chronic fluoxetine administration, recover the normal level of adult neurogenesis. Fluoxetine treatment increases the free concentration of the neurotransmitter serotonin and this monoamine is implicated in the regulation of the neurogenic process; however, the target of the action of this neurotransmitter has not been fully elucidated. In this study, we have tried to determine the relevance of the serotonin receptor 3 (5-HT3) in the hippocampal neurogenesis of adult rats. We have used fluorescent immunohistochemistry to study the expression of the 5-HT3 receptor in different neurogenesis stages in the SGZ, identifying its expression in stem cells, amplifying neural progenitors and immature neurons. Moreover, we have studied the impact of a 5-HT3 antagonist (ondansetron) in the fluoxetine-induced adult neurogenesis. We observed that fluoxetine alone increases the number of both proliferating cells (ki67 positive) and immature neurons (DCX positive) in the SGZ. By contrast, co-treatment with ondansetron blocked the increase in proliferation and neurogenesis. This study demonstrates that the activation of 5-HT3 receptors is necessary for the increase of adult neurogenesis induced by fluoxetine.